Shexiang Baoxin Pill, a Formulated Chinese Herbal Mixture, Induces Neuronal Differentiation of PC12 Cells: A Signaling Triggered by Activation of Protein Kinase A - Xu, Miranda Li; Zheng, Zhong-Yu; Xia, Ying-Jie; Liu, Etta Yun-Le; Chan, Stanley Ka-Ho; Hu, Wei-Hui; Duan, Ran; Dong, Tina Ting-Xia; Zhan, Chang-Sen; Shang, Xiao-Hui; Tsim, Karl Wah-Keung (Frontiers in Pharmacology, 2019)
Abstract Background: Shexiang Baoxin Pill (SBP) is a well-known composite formula of traditional Chinese medicine (TCM), and which is commonly used today in treating cardiovascular diseases. SBP consists of 7 materials thereof, including Moschus, extract of Ginseng Radix et Rhizoma, Bovis Calculus Artifactus, Cinnamomi Cortex, Styrax, Bufonis Venenum and Borneolum Syntheticum. Here, we are investigating the potential roles of SBP in inducing neuron differentiation, i.e. seeking possible application in neurodegenerative diseases. Methods: Water and ethanol extracts of SBP, denoted as SBPwater and SBPEtOH, respectively, as well as its individual herbal materials, were standardized and applied onto cultured rat pheochromocytoma PC12 cells. The potential effect of SBP extracts in neuronal differentiation was suggested by following parameters: (i) induction of neurite outgrowth of PC12 cells; (ii) increase of neurofilament expression; and (iii) activation of transcription of neurofilament. Results: The treatments of SBPwater and SBPEtOH, or extracts from individual herbal materials, with or without low concentration of nerve growth factor (NGF), could potentiate the differentiation of cultured PC12 cells. The differentiation was indicated by increase of neurite outgrowth, as well as expression of neurofilaments. In addition, application of H89, a protein kinase A (PKA) inhibitor, suppressed the SBP-induced neurofilament expressions, as well as the phosphorylation of cAMP-responsive element binding protein (CREB) in cultures. Conclusion: SBP is proposed to possess trophic activity in modulating neuronal differentiation of PC12 cells, and this induction is shown to be mediated partly by a cAMP-PKA signaling pathway. These results indicate the neurite-promoting SBP could be useful in developing potential drug in treating or preventing neurodegenerative diseases.